Antibacterial Test of Liquid Soap Preparations Rambutan Peel Extract (Nephelium lappaceum Linn) the Growth of Staphylococcus Aureus - Juvita Herdianty; Luluk Aniqoh Meliana Putri; Arif Wijayanto (Strada Journal of Pharmacy, 2022)
Long-term use of antibiotics leads to resistance. Rambutan fruit is a fruit which grows seasonally, but the utilization of the fruit skin is still lacking. Several studies have been carried out but limited to the flesh and leaves. The purpose of this study was to utilize rambutan peel waste into a liquid soap preparation and then carry out an antibacterial test against Staphylococcus aureus bacteria. The content of compounds from the skin of rambutan fruit (Nephelium lappaceium Linn) is thought to have antibacterial properties. The content test was carried out using a phytochemical screening method. The screening results of rambutan peel extract showed the presence of alkaloids, flavonoids, saponins, and tannins. The antibacterial test method used the well diffusion method with concentrations of 20% 40%, 60% positive control of Biore liquid soap and negative control of soap base. The test parameters for liquid soap preparations include: organoleptic test, homogeneity test, pH test, foam height. The results showed the best concentration of 60% had the ability as an antibacterial against Staphylococcus aureus.